EFFECT OF PROBLEM-BASED LEARNING (PBL) ON CRITICAL THINKING DISPOSITION IN SCIENCE EDUCATION - (:unkn) unknown (SCIBULCOM LTD, 2013)
What has been intended within the scope of this study is to inquire the influence of the problem-based learning, having been applied to the science teacher candidates from the first grade of Science Teaching Department, on the candidates critical thinking dispositions. Students with even student numbers comprised the experimental group (24 students) and other students with odd student numbers comprised the control group (22 students). In the experimental group, the General Physics II lesson was conducted with problem-based learning over the course of 14 weeks while it was conducted with the traditional method in the control group. The California Critical Thinking Disposition Inventory was used as the data collecting instrument. Data obtained by means of the data collecting instrument were subjected to statistical analysis with the SPSS package program. During the research, the lower dimension points of curiousness and systematicity and total points of critical thinking of the experimental group as a result of PBL they had received have significantly increased compared to the control group who had received traditional education. However, significant differences have not been observed between the experimental and control groups in the fields of critical thinking characteristics such as analyticity, open-mindedness, self-confidence and truth-seeking.
Keywords: learning environment; problem-based learning; critical thinking disposition; science education; teacher candidates